2022
DOI: 10.1186/s12872-022-02538-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcomes of postoperative tracheostomy in patients undergoing acute type A aortic dissection surgery

Abstract: Background Despite surgical advances, acute type A aortic dissection remains a life-threatening disease with high mortality and morbidity. Tracheostomy is usually used for patients who need prolonged mechanical ventilation in the intensive care unit (ICU). However, data on the risk factors for requiring tracheostomy and the impact of tracheostomy on outcomes in patients after Stanford type A acute aortic dissection surgery (AADS) are limited. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
(46 reference statements)
2
6
1
Order By: Relevance
“…The volume of intraoperative transfusion of RBCs was another independent risk factors for SH in our analysis results, which has also been reported previously (12,13,18). Although blood transfusion can be life-saving in cardiac surgery, increasing evidence suggests that massive transfusion of blood and blood products is associated with poorer clinical outcomes (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Nakajima et al found that the volume of transfused RBCs was positively associated with the risk of postoperative hypoxemia in patients undergoing surgery for acute type A aortic dissection, showing a dose-effect relationship (13).…”
Section: Discussionsupporting
confidence: 86%
“…The volume of intraoperative transfusion of RBCs was another independent risk factors for SH in our analysis results, which has also been reported previously (12,13,18). Although blood transfusion can be life-saving in cardiac surgery, increasing evidence suggests that massive transfusion of blood and blood products is associated with poorer clinical outcomes (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Nakajima et al found that the volume of transfused RBCs was positively associated with the risk of postoperative hypoxemia in patients undergoing surgery for acute type A aortic dissection, showing a dose-effect relationship (13).…”
Section: Discussionsupporting
confidence: 86%
“…Undergoing a tracheostomy is an important indicator of the increased risk of poor prognoses in patients undergoing cardiovascular surgeries [ 3 , 7 , 9 , 20 ], which was again confirmed in the current study. Due to the difference of surgical populations in different studies, the reported rates of POTs in the previous literature were quite different [ 3 , 7 , 8 , 9 , 10 , 11 ]. The overall incidence rate of POTs after HVS was 1.8% in our analysis, falling within the range of incidence rates reported in the previous literature [ 3 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 82%
“…As an important indicator of poor prognoses, POT operations often indicate a higher risk of mortality, prolonged hospital stay, increased medical burden, and declined quality of life [ 4 , 5 , 6 , 7 ]. The incidence of POTs varies widely in the previous literature due to the different surgical populations in different studies [ 3 , 7 , 8 , 9 , 10 , 11 ]. Compared to other surgical types, patients undergoing cardiovascular surgery have been reported to have a relatively higher POT rate, mostly in the range of 1.4–11.8% [ 3 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned risk factors were used to identify patients at greater risk for difficult weaning. Many of these factors were also combined and different mathematical models were elaborated to predict the need for prolonged mechanical ventilation or tracheostomy after cardiac surgery but, to the best of our knowledge, none of them has been validated in prospective studies [ 1 , 13 , 15 , 19 ]. Table 1 resumes the most recent studies on risk factors for prolonged ventilation and difficult weaning after cardiac surgery.…”
Section: Incidence Definition and Risk Factorsmentioning
confidence: 99%
“…Identification of patients that could benefit most from this intervention represents a major challenge in clinical practice. Some risk factors for tracheostomy after cardiac surgery have been identified, including heart failure, diastolic dysfunction, respiratory diseases, renal replacement therapy, emergency surgery, need for mechanical circulatory support, and re-doing surgery [ 19 , 70 ]. Moreover, independent predictors of mortality after tracheostomy in cardiac surgery patients were the duration of ventilation before tracheostomy and the presence of postoperative heart failure associated with respiratory failure, suggesting that careful evaluation of risks and benefits in these patients is of utmost importance [ 71 ].…”
Section: Prolonged Ventilation and Tracheostomymentioning
confidence: 99%